2010
DOI: 10.1117/1.3484748
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for optical clearing of collagenous tissues

Abstract: Abstract. Molecular interactions of optical clearing agents were investigated using a combination of molecular dynamics ͑MD͒ simulations and optical spectroscopy. For a series of sugar alcohols with low to high optical clearing potential, Raman spectroscopy and integrating sphere measurements were used to quantitatively characterize tissue water loss and reduction in light scattering following agent exposures. The rate of tissue water loss was found to correlate with agent optical clearing potential, but equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 29 publications
2
51
0
5
Order By: Relevance
“…In particular, hydrogen bond bridge formation disrupts the collagen hydration layer and facilitates water replacement by the OCA to perform RI matching. 36 In vivo studies were also performed in dorsal rat skin to evaluate OC, OC mechanisms and protein dissociation. 37 These studies have demonstrated that no collagen¯bers were dissociated or fractured at used OCA concentrations.…”
Section: Introduction and Basic Conceptmentioning
confidence: 99%
“…In particular, hydrogen bond bridge formation disrupts the collagen hydration layer and facilitates water replacement by the OCA to perform RI matching. 36 In vivo studies were also performed in dorsal rat skin to evaluate OC, OC mechanisms and protein dissociation. 37 These studies have demonstrated that no collagen¯bers were dissociated or fractured at used OCA concentrations.…”
Section: Introduction and Basic Conceptmentioning
confidence: 99%
“…collagen) and the ground matrix of soft tissue (e.g. interstitial fluid), by replacing water in the tissue with a fluid of a similar index of refraction as that of the proteins [9][10][11]. Measurements based on spectroscopy techniques, polarization or optical coherence microscopy as well as nonlinear imaging techniques such as two-photon fluorescence and second-harmonic generation (SHG) yield more valuable, otherwise virtually inaccessible information when performed on cleared (versus uncleared) soft biological tissue [12].…”
Section: Introductionmentioning
confidence: 99%
“…The second one might be from tissue shrinkage (less thickness) and corresponding spatial correlation of scatterers (more effective packing or ordering) caused by dehydration, which also gives clearing effect due to constructive interference in the forward direction of all scattered waves by spatially correlated collagen fibers, as is characteristic to an absolutely transparent eye cornea. 28 The last mechanism should correlate with more regular packing or ordering of scatterers, 11 which increase the anisotropy factor g. 31 For the molecular mechanism of dehydration caused by OCAs, Hirshburg et al 32,33 gave a reasonable explanation with the molecular dynamical simulation and demonstrated that the dehydration process is involved with the propensity of forming hydrogen bond bridges, which can be evaluated by collagen solubility of OCAs. 32 Besides the dehydration, the optical clearing agents entered into the dermis may induce collagen-fiber dissociation 33 or alteration of scatterer structure, 31 which also enhanced the optical clearing efficacy of skin.…”
Section: Correlation Between Dehydration and Optical Clearing Of Skinmentioning
confidence: 99%
“…28 The last mechanism should correlate with more regular packing or ordering of scatterers, 11 which increase the anisotropy factor g. 31 For the molecular mechanism of dehydration caused by OCAs, Hirshburg et al 32,33 gave a reasonable explanation with the molecular dynamical simulation and demonstrated that the dehydration process is involved with the propensity of forming hydrogen bond bridges, which can be evaluated by collagen solubility of OCAs. 32 Besides the dehydration, the optical clearing agents entered into the dermis may induce collagen-fiber dissociation 33 or alteration of scatterer structure, 31 which also enhanced the optical clearing efficacy of skin. All these or some other possible mechanisms do not take effect independently but interact on each other and contribute to the ultimate clearing efficacy together.…”
Section: Correlation Between Dehydration and Optical Clearing Of Skinmentioning
confidence: 99%
See 1 more Smart Citation